Physical and Chemical Properties of Bacterial Cellulose-Based Bioplastic Innovation from Sago Liquid Waste for Eco-Friendly Secondary Food Packaging - Aminah Maryani; Nur Arfa Yanti; La Ode Ahmad Nur Ramadhan; Reza Kurniawan (ALCHEMY Jurnal Penelitian Kimia, 2026)
The increasing demand for plastic food packaging has raised concerns over the environmental impact of plastic waste. Previous research has used sago liquid waste as a primary food packaging material, namely, edible coatings on tomatoes and edible films on sausages. However, research on secondary food packaging has not been conducted. The method used in this research involves a series of stages, from synthesizing bacterial cellulose to make bioplastics. The bioplastics were made with bacterial cellulose fermented from sago liquid waste and mixed with varying compositions of carboxymethyl cellulose (CMC), zinc oxide (ZnO), polyvinyl alcohol (PVA), and glycerol. Chemical characteristics, as determined by functional group analysis, showed that bioplastics still exhibited the typical functional groups of bacterial cellulose, as well as additional groups from glycerol, CMC, PVA, and ZnO, indicating the success of chemical structure modification in bioplastics. The crystallinity level of bioplastics also increased with the concentration of the mixture, with the highest crystallinity value of 37.084% in bioplastic sample A4. The physical characteristics of bioplastics, such as transparency, thickness, moisture content, water solubility, water uptake, and water vapor transmission rate, increased with increasing bioplastic mixture.